2003
DOI: 10.1038/sj.ijo.0802483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manipulated palatability on appetite depend on restraint and disinhibition scores from the Three-Factor Eating Questionnaire

Abstract: OBJECTIVES:The present study evaluated the effects of dietary restraint on short-term appetite in response to manipulated palatability. DESIGN: The effects of palatability on appetite during a lunchtime meal were assessed by contrasting intake of a bland and palatable version of a simple food (within subject). To test how responses to palatability varied with restraint, these meals consumed by women were classified according to restraint (R) and disinhibition (D) scores from the Three-Factor Eating Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 44 publications
5
27
1
Order By: Relevance
“…Although below the initially estimated thirty-two, this sample being more homogeneous than that in Blake et al (34) allowed the detection of significant differences (0?01 level). This was probably explained by narrower ranges in BMI and disinhibition scores in our sample compared with Blake et al's sample (38) .…”
Section: Participantscontrasting
confidence: 72%
“…Although below the initially estimated thirty-two, this sample being more homogeneous than that in Blake et al (34) allowed the detection of significant differences (0?01 level). This was probably explained by narrower ranges in BMI and disinhibition scores in our sample compared with Blake et al's sample (38) .…”
Section: Participantscontrasting
confidence: 72%
“…This cyclical pattern of restriction and overeating is reflected well in studies which demonstrate a 'disinhibition effect'. Here participants overeat (thus cannot maintain restraint over eating) in a variety of situations, such as being exposed to stress (37), in the presence of palatable food (16) and following a preload (11,38).…”
Section: Discussionmentioning
confidence: 99%
“…Herman and Polivy (48) postulated that restrained eaters develop anomalous eating patterns. Persons characterized as having high dietary restraint have been shown to report less hunger (49,50), be less sensitive to the satiety value of dietary fat (51), more responsive to external cues (24), and less responsive to food palatability (52). Burton-Freeman (25) showed that restrained persons have a blunted cholecystokinin response to a preload, suggesting an aberrant endocrine response to the ingestion of food.…”
Section: Discussionmentioning
confidence: 99%